Soft Sensor Based on Fusion Modeling with the Balanced Spatio-temporal Feature Network - Tang, Xiaochu; Wang, Yiting; Tao, Na; Yu, Yang (Chinese Control Conference, 2025)
In recent years, multi－feature integrated method based on deep neutral network has been widely applied to soft sensor． However, existing methods rarely consider the independence between feature extracted so that same features can be affected or even submerged．In this paper, a stacked variational autoencoder based on balanced spatio－temporal feature network（BST－ SVAE）is proposed to keep spatio feature and temporal feature in a balance state．In this way, the original features can be well preserved avoiding mutual influence．Firstly, a balanced parallel network including CNN and LSTM is used to design encoders and decoders to form a balanced spatio－temporal feature network．It can consider the interaction between internal relations and mine the time series relationship．Furthermore, stacked variational autoencoder（SVAE）is construed based on a balanced spatio－ temporal feature network．Finally, the proposed method is applied to the actual industrial process．Experimental results demonstrate the superiority and effectiveness of the proposed method．